Who's fit for the job? Allocating ministerial portfolios to outsiders and experts. Issue 4 (22nd November 2022) - Kaltenegger, Matthias; Ennser-Jedenastik, Laurenz
Abstract: Why do parties appoint outsiders and experts to ministerial positions? Extant research offers explanations based on institutional arrangements and external shocks (e.g. political or economic crises). We go beyond such system-level variables to argue that the characteristics of ministerial appointees are a function of the portfolio they are being appointed to. Drawing on theories of political delegation, we argue that outsider and expert appointments to ministerial office are affected by a portfolio's policy jurisdiction, its financial resources and appointment powers, and the partisan leanings of the ministerial bureaucracy. We test these arguments on all appointments of senior and junior ministers in Austria between 1945 and 2020. The analysis shows that outsiders are more likely to be appointed to ministries with greater party support in the bureaucracy, while experts are more likely appointed to portfolios dealing with high-salience issues.